Improvement of Oat as a Winter Forage Crop in the Southern United States. Issue 4 (1st July 2014) - Kim, Ki‐Seung; Tinker, Nicholas A.; Newell, Mark A.
ABSTRACT: Oat ( Avena sativa L.) is a cool season annual grass species produced for grain and forage in many countries. The majority of oat cultivars in the United States are spring types grown primarily for grain production. However, in the southern region of the United States, much of the oat production consists of winter types that are grown for grain or animal forage, and in some cases as a dual‐purpose crop. As with other small grain crops used for forage production, the improvement of grazing tolerance, forage yield, and forage quality have not been major goals in U.S. oat breeding programs even though oat forage is a rich source of protein, vitamin B1, phosphorus, iron, and other minerals. However, breeding and research efforts for oat have recently been revitalized because of increased awareness of the positive health benefits associated with oat consumed as a whole grain food. Strengthening the molecular approaches for forage oat breeding in the southern United States could have a large impact on cattle production systems and could increase the production area planted to oat. Although many of the molecular tools developed for the improvement of grain production could be applicable to winter forage oat breeding, the tools are currently an untapped resource within the forage breeding community. The objectives of this manuscript are to examine the production of forage oat, the current state of forage oat breeding, and how molecular tools could aid and strengthen the development of improved forage oat cultivars.